Constructive features energy supply system nissan leaf - Dzyubenko, A.; Zelenchuk, I.; Дзюбенко, О. А.; Зеленчук, І. Д.; Дзюбенко, А. А.; Зеленчук, И. Д. (Харківський національний автомобільно-дорожній університет, 2016)
The paper deals with the basic elements of an electric Nissan Leaf high-voltage battery. The principle of the Li-ion controller and sensors used has been analyzed.
Конструктивна особливість системи живлення nissan leaf
Конструктивная особенность системы питания nissan leaf
Keywords: electric car; Nissan Leaf; Li-ion battery; сcurrent sensors; high voltage battery; power supply system; електромобіль; Nissan Leaf; Li-ion акумулятор; датчик струму; високовольтна батарея; система електропостачання; электромобиль; Nissan Leaf; Li-ion аккумулятор; датчик тока; высоковольтная батарея; система электропитания; 621.313.333